Physicochemical and sensory characteristics of bread leaf enriched with Kiwicha (Amaranthus caudatus L.) and Cañihua (Chenopodium pallidicaule Aellen) - Chamorro-Gómez, Ruth Esther; Abad-Villar, Dani; Natividad-Bardales, Ángel David; Estacio-Laguna, Roger; Ríos-García, Geaninne; Muñoz-Garay, Sergio Grimaldo; Rojas-Portal, Ruben Max; Cueto-Rosales , César Robert; Villanueva-Tiburcio, Juan Edson (Revista Colombiana de Investigaciones Agroindustriales, 2023)
Bread is a widely consumed food, which has wheat as its basic ingredient; there are various formulations that include flour from different cereal sources. The objective of the research was to evaluate the effect of including Kiwicha (Amaranthus caudatus L.) and Cañihua (Chenopodium pallidicaule Aellen) on the physicochemical and sensory characteristics of bread leaf. The preparation of ​​bread leaf was developed with the direct dough method; the mixture was carried out with a simple mixture design and only the three formulations with the highest protein contents were selected., F1(trigo, Kiwicha, Cañihua: 73 %, 17 %, 10 %); F2 (wheat, Kiwicha, Cañihua: 73 %, 20 %, 7 %) and F3 (wheat, Kiwicha, Cañihua: 70%, 20%, 10%); F0 was considered as control: bread leaf made with 100% wheat flour. The physicochemical characteristics were analyzed using a complete randomized design (RCD), with Tukey’s test (p ≤ 0,05) and sensory properties with Friedman’s test (p ≤ 0,05). The results showed that the physicochemical characteristics were different (p ≤ 0,05) except for pH and titratable acids. The F3 formulation reported lower alanine content and higher leucine content with 0,10 to 1,79 g of amino acid (AA) per 100 g of protein pure, determined in (g/100 g of original sample and factor 6,25), respectively. In the bread crust, the L* color analysis was higher in formulation F3 (50,0) (p ≤ 0,05) while the other formulations F1 and F2 varied. Sensorily, the F0 treatment had greater acceptability, however, in the prepared breads (F1, F2 and F3) the content of iron, amino acids and macronutrients stands out. It is concluded that breads made with the addition of Kiwicha and Cañihua to the flour formulation are a good source of proteins, iron, and amino acids.